2016
DOI: 10.1155/2016/8304524
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Profiles ofMycobacterium ulceransIsolates to Streptomycin and Rifampicin in Two Districts of the Eastern Region of Ghana

Abstract: Background. Drug resistance is a major challenge in antibiotic chemotherapy. Assessing resistance profiles of pathogens constitutes an essential surveillance tool in the epidemiology and control of infectious diseases, including Buruli ulcer (BU) disease. With the successful definitive management of BU using rifampicin and streptomycin, little attention had been paid to monitoring emergence of resistant Mycobacterium ulcerans (M. ulcerans) isolates in endemic communities. This study investigated the susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…tuberculosis . Current methodologies to perform susceptibility testing against clinical isolates are often time consuming and cumbersome (use of agar proportion methods), thus, requiring several months to generate results [6, 8, 26]. Improvements have been introduced using luminescent reporter strains [45]; however, this technology is limited to specific engineered strains and cannot be widespread applied to clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tuberculosis . Current methodologies to perform susceptibility testing against clinical isolates are often time consuming and cumbersome (use of agar proportion methods), thus, requiring several months to generate results [6, 8, 26]. Improvements have been introduced using luminescent reporter strains [45]; however, this technology is limited to specific engineered strains and cannot be widespread applied to clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an alternative drug regimen would be required to treat resistant M . ulcerans strains [26], even though the emergence of resistance in M . ulcerans might follow different dynamics compared to M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…investigated the susceptibility profiles of 70 MU isolates from 2 BU endemic areas in Ghana to SR at critical concentrations of 40 μg/mL and 4 μg/mL, by the Canetti proportion method. The authors reported 17.1% resistance to rifampicin and 2.9% to streptomycin . The outcome although does not reflect all BU endemic areas, still it is essential for antibiotic stewardship in terms of disease surveillance and control.…”
Section: Prolong Viability Of Mu In Bu Lesionsmentioning
confidence: 90%
“…These diseases continue to be major global health concerns, due to a marked increase in the number of susceptible individuals (Bruchfeld et al, 2015;Chao et al, 2020;Amoako et al, 2021) and associated prejudicial direct and secondary effects on global health and economy (Saraya et al, 2012). Moreover, the increasing antimicrobial resistance limits the efficacy of the reduced number of compounds available for treatment, stressing the need for expansion of surveillance and development of novel therapeutic and disease control strategies (Owusu et al, 2016;Gygli et al, 2017;Cambau et al, 2018).…”
Section: The Burden Of Mycobacterial Diseasesmentioning
confidence: 99%